Physiological responses of race car drivers in authentic and simulated motor-racing - Justin Holland; Megan Davis; David Ferguson (Frontiers in Sports and Active Living)
ObjectivesThe aim of the present investigation was to determine the influence of G-loading and psycho-emotional stress and competitive pressures on driver physiology between authentic and simulated racing during similar environmental conditions (e.g., a hot cockpit).MethodsAuthentic racing data was collected during the 2018 “Sahlen's 6 h at the Glen” race, where five male drivers (age = 38.0 ± 5.1 y, driving years = 8 y) competed in the IMSA GTD class in 1 h stints over the course of the race. In the simulated race, the same drivers wore a full protective outfit to replicate the attire worn in the authentic race for 60 min in an environmental controlled room that matched authentic racing. During authentic and simulated racing physiological measures of heart rate (HR), breathing rate, physiological strain index (PSI), skin temperature and core temperature were recorded.ResultsIn the final 50 min higher (P < 0.05) physiological demands were observed in core temperature, PSI, and breathing rate for authentic racing compared to simulated racing. HR in the final 50 min was higher (P < 0.001) in authentic racing (159 ± 23 beats·min−1) to simulated racing (112 ± 19 beats·min−1) with no increase in heart rate in the first 10 min of simulated racing. In authentic racing skin temperature was higher (P < 0.001) in the first 10 min compared to simulated racing however, in the final 50 min there was no difference (P = 0.928) observed.ConclusionsG-loading and psycho-emotional stress lead to considerable increases in metabolic work and physical stress in authentic racing compared to simulated racing. A racing simulator does not generate the physical loads to drive the car or the psycho-emotional stress and competitive pressure of an authentic racing event.